2008
DOI: 10.1002/hbm.20618
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of retrieval‐related activity in lateral parietal cortex: Evidence from fMRI and ERPs

Abstract: The present study addressed the question whether neural activity in left lateral parietal cortex is modulated by amount of information recollected. In two experiments (one using fMRI, the other ERPs) subjects first studied pairs of pictures presented for either one or six seconds. They then performed a standard 'Remember/Know' recognition memory test in which the old items comprised one of the pictures from each studied pair. In both experiments, a surprise post-test indicated that subjects recollected more de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
105
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 45 publications
19
105
2
1
Order By: Relevance
“…In addition, one cluster in the parahippocampal cortex was revealed only in the reversed > new contrast with an activation pattern that is very similar to the one observed in the hippocampus. All these regions were previously identified as being associated with recollective processing (e.g., Dobbins, Rice, Wagner, & Schacter, 2003;Henson et al, 2005;Henson, Rugg, Shallice, Josephs, & Dolan, 1999;Vilberg & Rugg, 2009;Yonelinas et al, 2005). Thus, these results are in line with the prediction that associative recognition of word pairs which were studied as separate lexical items within sentence frames recruits a network typically associated with recollection.…”
Section: Flexible Recollection In the Sentence Groupsupporting
confidence: 86%
“…In addition, one cluster in the parahippocampal cortex was revealed only in the reversed > new contrast with an activation pattern that is very similar to the one observed in the hippocampus. All these regions were previously identified as being associated with recollective processing (e.g., Dobbins, Rice, Wagner, & Schacter, 2003;Henson et al, 2005;Henson, Rugg, Shallice, Josephs, & Dolan, 1999;Vilberg & Rugg, 2009;Yonelinas et al, 2005). Thus, these results are in line with the prediction that associative recognition of word pairs which were studied as separate lexical items within sentence frames recruits a network typically associated with recollection.…”
Section: Flexible Recollection In the Sentence Groupsupporting
confidence: 86%
“…The first reports of parietal old/new effects came from studies using electroencephalography, which revealed event-related potentials (ERPs) that differed in amplitude over (primarily left) lateral parietal scalp sites in response to hits relative to CRs, with an onset of around 400 ms post-stimulus (for review, see Rugg and Curran 2007). A rich body of evidence suggests that this effect reflects the recollection of contextual details from an episode, rather than simple item familiarity (e.g., Smith 1993;Wilding et al 1995;Allan et al 1998;Curran 2000;Curran and Cleary 2003;Woodruff et al 2006;Vilberg and Rugg 2008a).…”
Section: Ventral Ppcmentioning
confidence: 99%
“…It has been suggested that the effect is sensitive to the amount of information recollected (Vilberg & Rugg, 2009;Vilberg, Moosavi, & Rugg, 2006;Wilding, 2000), although the relevant evidence comes from judgments of recollected details rather than manipulations of associative fan. Likewise, Nyhus and Curran (2009) found that the parietal old/ new effect interacted with associative fan.…”
Section: Probe Typementioning
confidence: 99%